2008
DOI: 10.1007/s00420-008-0306-4
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress and depression in Korean employees

Abstract: The finding that inadequate social support and discomfort in occupational climate is a better predictor of depressive symptoms than organizational injustice in Korea, indicates that the newly developed KOSS has cultural relevance for assessing occupational stress in Korea. Future studies need to understand factors such as "emotional labor" within certain industries where increased risk for depression is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 52 publications
5
76
0
3
Order By: Relevance
“…Previous studies showed that transportation industry had associations with depression 47,48) . Socioeconomic status such as education and personal income might affect our results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that transportation industry had associations with depression 47,48) . Socioeconomic status such as education and personal income might affect our results.…”
Section: Discussionmentioning
confidence: 99%
“…However, "discomfort in occupational climate" and "inadequate social support" seem to be more important stressors for Korean workers 17) . Recent study using KOSS document that in contrast to western studies of occupational stress, "inadequate social support" and "discomfort in occupational climate" are the most powerful predictors and are more predictive of depression than either job demands or job control 22) . The aim of this study was to investigate the association between insomnia and job stress assessed by the KOSS in employees recruited from a nationwide sample in Korea, and then to analyze which components of occupational stress is more strongly associated with insomnia in Korea.…”
mentioning
confidence: 92%
“…Another meta-analysis reported that high work demands, low autonomy, lack of reward, and job insecurity increase the risk of burnout [2] . In a study conducted in South Korea, lack of social support, job insecurity, and uncomfortable workplace environment were found to be risk factors for depression [3, 4]. In a systematic review study, the following three categories of work-related factors that contribute to the development of mental health problems were identified: unbalanced employment design, job uncertainty, devaluation, and disrespect in the workplace [5].…”
Section: Introductionmentioning
confidence: 99%